NILAI BUDAYA DALAM LEGENDA LIANG AYAH DI KALIMANTAN TENGAH: KAJIAN FOLKLOR - Desy, Winda Oktovina; Mursalim, Mursalim; Hanum, Irma Surayya (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
Folk stories have cultural values that are used by the community as a picture of actions in everyday life. This study aims to find out the cultural values contained in the legend of the father-in-law so that it can be used as learning in life. This research was included in the field research using qualitative descriptive research. The source of data in this study was an informant named Kasman. The cultural value of human relations with God is manifested in the form of wara and karma ceremonies. The cultural value of human relations with nature is manifested in the form of riverside villages, hunting, and using plants. The cultural value of human relations with society is manifested in the form of joint learning, ceremony invitations, the search for spouses, togetherness in ceremonies. The cultural value of human and other human relationships is manifested in the form of cooperation, affection, friendship, respect, and cultural values of human relations with oneself manifested in the form of intelligence, responsibility, worry, and not thinking.